(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What challenges did students recognize in the sudden transition to e-learning due to the outbreak of COVID-19? Which suggestions facilitated in the improvement of implementing e-learning and to what extent did the students think that following their recommendations contributed to better e-learning? Purpose: With the research, we wanted to determine what challenges students at higher vocational schools perceived during the e-learning process. Due to the sudden appearance of COVID-19, the educational approach swiftly changed, and both teachers and students were faced with many challenges. Method: Content analysis was used on domestic and international research studies. The literature was reviewed and analyzed using keywords. For the empirical research, we collected data by surveying students from the southeastern part of Slovenia in seven different short cycle higher education programs. The questionnaire was designed based on self-evaluation reports and previously analyzed professional literature dealing with this area. Results: Results are depicted based on the challenges that students faced in the sudden onset of e-learning due to the pandemic. By following recommendations provided by students, teachers were able to improve their e-learning approach, in which everyone was involved, and thus facilitated the learning process. Organization: The results of the research enable schools to implement the identified challenges that students perceived during the educational process to improve e-learning. The research findings portray a possible answer on what needs to be improved in e-learning and how to adapt approaches in a way that is tailored to the student. Society: Recognizing students’ e-learning challenges is the foundation for improving the entire e-learning process, which contributes to better achievement of educational goals and greater contribution of knowledge to society. Originality: Several studies on e-learning have already been conducted, but we have not found any that address the challenges posed by short cycle higher education students in the face of the immediate and unexpected introduction of e-learning due to the global health situation. Limitations/Future Research: We have limited ourselves to research that has already been conducted in this area. The resulting questionnaire was created as a pilot survey on a larger sample to determine reliability and to obtain a starting point for implementing improvements in practice and the possibility of further testing on an even larger number of students. The research also offers a starting point for the preparation of a questionnaire intended for higher education teachers who already have conducted e-learning.